From perceived autonomy support to intentional behaviour: Testing an integrated model in three healthy-eating behaviours. (1st January 2016) - Girelli, Laura; Hagger, Martin; Mallia, Luca; Lucidi, Fabio
Abstract: A motivational model integrating self-determination theory, the theory of planned behaviour, and the health action process approach was tested in three samples in three behavioural contexts: fruit and vegetable, breakfast, and snack consumption. Perceived support for autonomous (self-determined) forms of motivation from parents and autonomous motivation from self-determination theory were hypothesised to predict intention and behaviour indirectly via the mediation of attitude and perceived behavioural control from the theory of planned behaviour. It was also expected that planning strategies would mediate the effect of intention on behaviour. Relations in the proposed models were expected to be similar across the behaviours. A two-wave prospective design was adopted. Three samples of high-school students (total N = 1041; 59.60% female; M age = 17.13 years ± 1.57) completed measures of perceived autonomy support, autonomous motivation, theory of planned behaviour constructs, planning strategies and behaviour for each of the three behavioural contexts. Three months later, 816 participants (62, 24% female; M age: 17.13 years, SD = 1.58) of the initial sample self-reported their behaviour referred to the previous three months. Structural equation models provided support for the key hypothesised effects of the proposed model for the three health-related behaviours. Two direct effects were significantly different across the three behaviours: the effect of perceived autonomy support on perceived behavioural control and the effect of attitude on intention. In addition, planning strategies mediated the effect of intention on behaviour in fruit and vegetable sample only. Findings extend knowledge of the processes by which psychological antecedents from the theories affect energy-balance related behaviours. Highlights: A motivational model integrating SDT, TPB and HAPA was tested on eating behaviours. Overall, the model predicted behaviour for F&V, breakfast and snacking contexts. Some effects were significantly different across the three behaviours. Planning mediated the intention–behaviour relation in F&V sample only.